International perspectives on sustainability reporting - Buallay, Amina (Emerald Publishing, 2022)
As global concerns grow surrounding the environment, climate, and sustainability, International Perspectives on Sustainability Reporting presents business case studies from different sectors across different regions, highlighting the changing institutional contexts and laws in each country regarding sustainability reporting